What Now: The Role of Attitude and Communicative Actions When Making Decisions During a Disease Crisis - Ashley McLeod-Morin; Lauri Baker; Angela B. Lindsey; Lisa K Lundy; Ricky Telg (Journal of Applied Communications, 2023)
During a crisis such as the COVID-19 pandemic, organizations often communicate about a risk to encourage people to take particular protective actions, and the decision-making process about protective actions can be especially complex. It is important to determine how organizations can encourage specific behaviors and, as such, this study sought to investigate how attitudes and communicative actions influenced behavior related to recommendations from the CDC during the COVID-19 pandemic. To address the purpose of this study, an online quantitative survey was distributed to United States residents during the COVID-19 pandemic. Results from this study reveal that attitude and transmission and acquisition communicative actions are good predictors of behavior. Organizations should prioritize improving target audience’s attitude toward the organization since this will likely lead to supportive behaviors during an infectious disease outbreak.
Keywords: Communicative actions; decision-making behaviors; crisis communication; disease outbreak; COVID-19